Electronic Elections : The Perils and Promises of Digital Democracy - Alvarez, R. Michael, 1964- (Book collections on Project MUSE., 2008)
Since the 2000 presidential election, the United States has been embroiled in debates about electronic voting. Critics say the new technologies invite tampering and fraud. Advocates say they enhance the accuracy of vote counts and make casting ballots easier--and ultimately foster greater political participation. Electronic Elections cuts through the media spin to assess the advantages and risks associated with different ways of casting ballots--and shows how e-voting can be the future of American democracy. Elections by nature are fraught with risk. Michael Alvarez and Thad H.